The COP28 Controversy and Its Impact on Indonesia as a Developing Country - nurdin, rafi (Frequency of International Relations (FETRIAN), 2025)
The COP28 conference is a multilateral forum that brings together nearly 200 countries to respond to the urgency of the global climate crisis through a shared commitment to the transition from fossil fuels to environmentally friendly energy. In this conference, Indonesia not only acts as an active participant, but also as a representative of developing countries that face challenges in implementing the energy transition. Even though it is an important country in COP28, Indonesia's position as a developing country at this conference means that Indonesia remains one of the countries that is likely to be affected by a number of controversies behind the existence of COP28, especially exploitation planned by the host and developing countries that are participants. This research aims to understand Indonesia's contribution to COP28, the controversy that occurred at this conference, and the impact of the existing controversy on Indonesia as a developing country.